On the Convergence of the Relaxation Methods for Positive Definite Linear Systems (Journal of Computational Mathematics, 2021)
We establish the convergence theories of the symmetric relaxation methods for the system of linear equations with symmetric positive definite coefficient matrix, and more generally, those of the unsymmetric relaxation methods for the system of linear equations with positive definite matrix.